Expression of VEGF, PD-ECGF, and VEGF-C and its clinicopathologic significance in oral squamous cell carcinoma - OHYAMA, Kazuhiko; YOSHIHAMA, Yasuto; SASAKI, Akira; NAKAYAMA, Shuko; YOSHIOKA, Norie; SHIMO, Tsuyoshi; KISHIMOTO, Koji; MANDAI, Toshiko (Japanese Journal of Oral and Maxillofacial Surgery, 2005)
This study investigated the relation between the expression and clinicopathlogic significance of VEGF, PD-ECGF, and VEGF-C in oral squamous cell carcinoma (OSCC). The expression of these angiogenic factors in OSCC specimens from 62 patients was examined by immunohistochemistry. VEGF expression significantly correlated with lymph node metastasis, histologic differentiation, and mode of invasion (p<0.05), but not with age, sex, tumor size, or vessel invasion. PD-ECGF expression significantly correlated with age and mode of invasion (p<0.05), but not with sex, tumor size, lymph node metastasis, histologic differentiation, or vessel invasion. VEGF-C expression strongly correlated with the lymph node metastasis (p<0.01), but not with the other factors. Logistic regression analysis of lymph node metastasis was performed. Univariate analysis showed that lymph node metastasis correlated with mode of invasion, VEGF-C, VEGF, and vessel invasion (p<0.05). Multivariate analysis of these four factors revealed that mode of invasion and VEGF-C were exclusive independent factors influencing lymph node metastasis (p<0.05). Angiogenic factor-positive cases showed higher microvessel density (MVD) than negative cases, and only PDECGF expression statistically correlated with MVD. Univariate analysis of overall survival showed that VEGF, lymph node metastasis, tumor differentiation, and mode of invasion were significant prognostic factors. Moreover, multivariate analysis of these four factors with Cox's proportional hazards model revealed that VEGF and lymph node metastasis were independent predictors of outcome. The 5-year cumulative survival rate by the Kaplan-Meier method was 54.9 % for the VEGF-positive group and 90.5 % for the VEGF-negative group. The VEGF-positive group showed a significantly lower survival rate than the VEGF-negative group (p<0.01). These results indicate that VEGF and VEGF-C may be a reliable predictors of outcome and regional lymph node metastasis, respectively. Moreover, VEGF and VEGF-C may be important factors for developing new diagnostic systems for prognosis and metastasis in OSCC, respectively.